What’s for Dinner? How Factors that Potentially Influence Self-Efficacy Affect the Dietary Habits of Low-Income African American Mothers - Nozella L. Brown (Adult Education Research Conference, 2014)
This multi-site qualitative bounded case study explored factors that affected the dietary habits of low-income African American mothers. Using the theoretical framework of social cognitive theory and critical race theory, the findings captured the behavioral, personal, and environmental factors 15 mothers perceived as influencing their dietary habits.